Pediatric Radiotherapy Planning and Treatment. Issue 4 (28th March 2014) - Smilowitz, Jennifer
Abstract : Pediatric Radiotherapy Planning and Treatment. Olch A. J., CRC Press, Taylor & Francis Group, Boca Raton, FL, 2013. Hardcover 374 pp. Price: $149.95. ISBN: 978‐1‐4200‐8509‐9.